β-glucan in the lymph nodes in sarcoidosis and in Kveim-Siltzbach test reagent - Tercelj, Marjeta; Salobir, Barbara; Rylander, Ragnar (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2017)
Background: Previous studies have demonstrated a relationship between biomass of fungi exposure in the home and the risk of sarcoidosis. β-glucan was present in the bronchial alveolar lavage fluid (BALF) of patients with sarcoidosis. The Kveim-Siltzbach test reagent (KSTR) induces a sarcoidosis specific, granulomatous, cutaneous response and was used to establish the diagnosis. To date, the granuloma-inducing component of KSTR is still unknown. The present study was undertaken to investigate the presence of β-glucan in the lymph nodes of patients with sarcoidosis and to determine the relationship between the amounts of this agent with disease severity and to investigate the presence of β-glucan in KSTR. Materials and methods: Lymph node aspirations were collected by transbronchial needle aspiration (TBNA) in region R4 or 7 from patients with newly diagnosed sarcoidosis. The samples were treated to isolate β-glucan and analyzed using a Limulus-based assay. Cultures of Propionibacterium ac. and Mycobacterium gordonae as well as samples of Kveim-Siltzbach test reagent were analyzed to determine β-glucan content. Results: A significant relationship was observed between the amount of the β-glucan in the lymph nodes and the extent of granuloma formation in the lung parenchyma, and the size of the lymph nodes in the mediastinum (r=0.787, p=0.0001 and r=0.664, p<0.001 respectively, Spearman’s test). The samples of Kveim-Siltzbach test reagent contained high levels of β-glucan. Cultures of Propionibacterium ac. and Mycobacterium gordonae contained β-glucan, the levels of which were lower in the Mycobacterium cultures. Comments: The results support the hypothesis that β-glucan, and thus fungal exposure, are involved in the pathogenesis of sarcoidosis.